Pelatihan Kepemimpinan dan Pendidikan Karakter untuk Guru dan Siswa di Sekolah Binaan Berbasis Game Edukasi - Permana, Agus Aan Jiwa; Kertiasih, Ni Ketut; Sindu, I Gede Partha; Wijaya, I Gede Saputra Wahyu; Setemen, Komang; Pracasitaram, I Gede Made Surya Bumi; Pageh, I Made (Al-DYAS, 2024)
Leadership training and character education for teachers in assisted schools is carried out to improve the quality of education through increasing leadership abilities and instilling character values. As educators and classroom leaders, teachers have a major impact on students' intellectual and moral development. Therefore, this training is designed to provide the skills and knowledge needed so that teachers can become leaders and shape students' strong character and integrity. This program includes leadership theory, effective communication techniques, conflict management, getting to know one's identity, as well as strategies for developing student character according to the independent curriculum. The approach used combines active learning methods such as group discussions and case studies, so that teachers can apply the concepts learned in real contexts. The main focus is on developing student character through values ​​such as honesty, responsibility, empathy and cooperation. This training can improve the leadership competence of school principals and classroom teachers, create a positive school environment, and produce the next generation with strong character and harmony. Students are expected to be able to have better character in the future in knowing themselves, culture, the environment and nationalist spirit.